Acid Activated Shrimp Shell Derived Hydrochar for Adsorptive Removal of Anionic Direct Blue 71 Dye from Aqueous Solutions - Do, Danh Quang; Bui, Thi Hang; Nguyen, Quang Hung; Nguyen, Thi An Hang (Journal of Water and Environment Technology, 2025)
The Direct Blue 71 (DB71) dye can pose risks to the life of aquatic flora, fauna, and human beings, owing to its toxic, carcinogenic, and mutagenic nature. Hence, this study fabricated and applied acid-activated shrimp shell-derived hydrochar (A-WSH) for the adsorptive removal of anionic DB71 from aqueous solutions. The effects of adsorption conditions on DB71 sequestration by A-WSH were evaluated. Characterization and modeling methods were utilized to elucidate the DB71 adsorption behaviors and mechanisms of A-WSH. Results showed that DB71 adsorption by A-WSH was optimized at pH 6.78, contact time of 4 h, adsorbent dose of 1 g/L, room temperature of 300 K, and shaking speed of 120 rpm. The isotherm data were best described by the Langmuir model with the DB71 maximum adsorption capacity of 156.25 mg/g. The kinetic data were more satisfactorily represented by Pseudo-second-order model than the Pseudo-first-order model. Thermodynamic and characterization results revealed that DB71 adsorption by A-WSH was endothermic and chemisorption. The A-WSH can be a promising DB71 adsorbent, thanks to high adsorption capacity, short equilibrium time, and no pH adjustment requirement. This study has opened up a novel pathway for the valorization of shrimp shells and remediation of DB71-contaminated aqueous solutions.